Food service and catering management : a practical guide (Manila, Philippines : Anvil Publications, 2004)
This book was a conceptualized to serve as a reference for such people, individual who have affinity for food and cooking - culinary enthusiast, entrepreneurs, teachers, demonstrators, students as well as the chefs and cooks who need to refresh their memories with some principles and procedures.
Chapter1. Food Knowledge -- Chapter2. Food Sanitation and Hygiene -- Chapter3. How to Get Started in a Catering Business -- Chapter4. Catering Facilities -- Chapter5. Catering Personnel -- Chapter6. Menu and Menu Planning -- Chapter7. Food Services -- Chapter8. Customer Goodwill and Food Service Ethics -- Chapter9. Recipe Quantification -- Chapter10. Contracting for Catering Functions.
Includes bibliographical references.
Keywords: KITCHEN TOOLS